Penelitian Kualitatif Terhadap Hukum Empiris - Dadang Sumarna; Ayyub Kadriah (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
Abstract separation of law between the normative aspects that stand outside of the social phenomena will mislead our analysis about the law, because the social facts are needed as the runway for legal development so there we need for awareness about normative legal research studied in complementary empirical legal research. . in methodical empirical legal research it is often limited to data collection that goes a long way and is misinterpreted as quantitative research, where in fact what is claimed as a quantitative empirical legal research is actually examined qualitatively so it is necessary to explain explicitly how the pattern of empirical legal research is and how the approach Qualitative research was conducted on empirical researchers. So it can be concluded that empirical legal research also opens up the possibility to be examined qualitatively with material collection methods such as interviews, court observations and analyzing archival records is a way of collecting qualitative empirical legal research data which uses expert interview methods. to collect empirical qualitative data, and it can be concluded that from yin shows that empirical legal analysis has shifted from dichotomies and purely quantitative cages and where there are alternative data collection options according to paton in empirical research that can use data collection methods that can be referred to as